Benefits of a Decentralized, Wind-Optimal Routing Structure in the North Atlantic Airspace - Nyessen, Nino (author) (2022)
In an effort to increase the operational efficiency in the North Atlantic region, the benefits of a decentralized, wind-optimal routing structure are researched. Such a routing structure allows for direct routing by optimizing trajectories on the individual level. Implementing a tactical conflict detection and resolution method eliminates the capacity limits imposed by air traffic control by shifting control to the flight deck. The benefits in terms of safety, capacity, and efficiency are assessed by comparing this routing structure to the current routing structure by simulating a year of real flight data. Furthermore, it is researched if such a routing structure remains viable for forecasted traffic levels by creating a future direct routing scenario with the use of dummy flights. Trajectory optimization is performed for the part of the trajectory above 10,000 ft in a decoupled manner with the ordered upwind algorithm for the horizontal domain and the base of aircraft data performance model for the vertical domain. Conflicts are solved on the tactical level with the modified voltage potential method in the horizontal domain. On average, a 5.1% fuel reduction, or 1.9% time reduction, is established for the new routing structure. A total of 18 loss of separations with an intrusion severity above 1% occur, of which the most severe intrusion still assures 734 ft vertical and/or 3.67 NM horizontal separation. The routing structure appears to be robust for future traffic levels as the airspace density scales linearly with the amount of aircraft and the conflict to loss of separation ratio remains constant with only three loss of separations slightly exceeding the 1% limit. Aerospace Engineering